The Effect of Motor Relearning Program on Daily Living Activity and Dynamic Balance in Non-Hemorrhagic Post Stroke Hemiparese Patients at Grandmed Lubuk Pakam Hospital - Jehaman, Isidorus; Br Siagian, Khairunnisa; Bintang, Siti Sarah; Ginting, Raynald Ignasius; Ginting, Rosita; Harefa, Karnirius (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2023)
Stroke is a functional disorder of the brain that can occur suddenly or abruptly with focal or global neurological signs that can last 24 hours or more (if no surgery or death occurs) without any signs of non-vascular causes, which include signs of subarachnoid hemorrhage, intracerebral hemorrhage, ischemia or cerebral infarction. This can cause disturbances in vital brain functions such as coordination disorders, balance disorders, posture control disorders, sensation disorders and movement reflex disorders, thereby reducing the ability to carry out daily living activities and balance disorders. The motor relearning program method is a program for retraining specific motor controls by avoiding unnecessary or wrong movements that involve cognitive processes, the application of motor and psychological science, training, understanding of nervous anatomy and physiology and is not based on the theory of normal development (neuro development). The research aims to determine the effect of the motor relearning program on daily living activities and dynamic balance disorders in post-stroke patients. The method used in this research is a quasi experiment with one group pretest and post test design. The research sample consisted of 9 people. The samples will be observed and adjusted to the specified criteria so that they do not cause problems. Each respondent was measured 2 (two) times, namely before and after the intervention. Test the hypothesis using the Wilcoxon test. The research results obtained a value of p = 0.000 (p=<0.05), which means there is a significant influence of the motor relearning program intervention on daily living activities and dynamic balance disorders in post-stroke patients. The results of this research can be concluded that the motorbike relearning program can improve daily living activities and dynamic balance disorders in patients after non-hemorrhagic stroke. It is hoped that the results of this research can contribute to health services for the community in overcoming the problems of daily living activities and dynamic balance disorders in post-stroke patients.